2018
DOI: 10.1016/j.celrep.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia Mediate Diverse Kinase Inhibitor Resistance Mechanisms in Cancer

Abstract: SummaryPrimary cilia are microtubule-based organelles that detect mechanical and chemical stimuli. Although cilia house a number of oncogenic molecules (including Smoothened, KRAS, EGFR, and PDGFR), their precise role in cancer remains unclear. We have interrogated the role of cilia in acquired and de novo resistance to a variety of kinase inhibitors, and found that, in several examples, resistant cells are distinctly characterized by an increase in the number and/or length of cilia with altered structural fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 38 publications
6
64
0
1
Order By: Relevance
“…Our results may be similar to what was observed in various pharmacologically drug-resistant human cancer cell lines (e.g., HCCC4006 lung adenocarcinoma, A549 lung carcinoma, rhabdoid tumor A204 and Dasatinib-resistant subline DasR), in which apparent ciliary tip fragmentation was described [ 51 ]. However, those studies found that the fragment tips contained both Arl13b and aaTub, whereas we and others have found that the Arl13b + vesicles are weak or negative for aaTub [ 42 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our results may be similar to what was observed in various pharmacologically drug-resistant human cancer cell lines (e.g., HCCC4006 lung adenocarcinoma, A549 lung carcinoma, rhabdoid tumor A204 and Dasatinib-resistant subline DasR), in which apparent ciliary tip fragmentation was described [ 51 ]. However, those studies found that the fragment tips contained both Arl13b and aaTub, whereas we and others have found that the Arl13b + vesicles are weak or negative for aaTub [ 42 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, abnormalities in ciliary length and morphology are known to disturb signal transduction mediated by the primary cilium, 97 99 so it may be worth comparing cilia lengths between GBM and normal samples and its potential impact on signalling. On this point, a recent work by Jenks and colleagues 100 revealed that drug-resistant cancer cells show increased cilia frequency and length, cilia tip fragmentation and also enhanced Shh activation, which undoubtedly reinforces this line of research in GBM. On the other hand, it is tempting to speculate on the following issue: Does the primary cilium release extracellular vesicles in the context of GBM?…”
Section: Resultsmentioning
confidence: 65%
“…The recent report that manipulating ciliary length/integrity in different drug-resistant cancer cell lines re-sensitizes them to appropriate RTK inhibitors could represent a promising strategy to explore in the context of GBM. 100 Finally, it might be interesting to consider strategies based on inhibiting histone deacetylase 6 (HDAC6) to restore primary cilia in GBM, since HDAC6 activation and ciliary loss seem to be common events in a variety of cancers 38 and HDAC inhibitors are emerging as a promising group of epigenetic agents for GBM treatment. 108 , 109 We expect that the outbreak of primary cilium as a key mediator of GBM will bring exciting new findings over the coming years that positively impact patient survival.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several compounds, including a panel of glucocorticoids, were found to be able to re-establish PC expression in cancer cell lines and attenuate their proliferation. A distinct approach is suggested in a recent study describing that PC can mediate resistance of cancer cell lines to kinase inhibitors [124]. The resistance to kinase inhibitors in tumor cells was associated with increased number and length of primary cilia and elevated Hh signaling.…”
Section: General Considerations and Remarksmentioning
confidence: 99%